Tropical Fruit Pulps: Processing, Product Standardization and Main Control Parameters for Quality Assurance - Silva,Carlos Eduardo de Farias (2017)
ABSTRACT Fruit pulp is the most basic food product obtained from fresh fruit processing. Fruit pulps can be cold stored for long periods of time, but they also can be used to fabricate juices, ice creams, sweets, jellies and yogurts. The exploitation of tropical fruits has leveraged the entire Brazilian fruit pulp sector due mainly to the high acceptance of their organoleptic properties and remarkable nutritional facts. However, several works published in the last decades have pointed out unfavorable conditions regarding the consumption of tropical fruit pulps. This negative scenario has been associated with unsatisfactory physico-chemical and microbiological parameters of fruits pulps as outcomes of little knowledge and improper management within the fruit pulp industry. There are protocols for delineating specific identity and quality standards (IQSs) and standardized good manufacturing practices (GMP) for fruit pulps, which also embrace standard operating procedures (SOPs) and hazard analysis and critical control points (HACCP), although this latter is not considered mandatory by the Brazilian legislation. Unfortunately, the lack of skilled labor, along with failures in complying established protocols have impaired quality of fruit pulps. It has been necessary to collect all information available with the aim to identify the most important hazards within fruit pulp processing lines. Standardizing methods and practices within the Brazilian fruit pulp industry would assurance high quality status to tropical fruit pulps and the commercial growth of this vegetal product towards international markets.